The Role of Education in Increasing the Success of Gold Investment in Gunungsitoli - Calvin Andika Telaumbanua; Asilika Waruwu; Franky Kristian Mendrofa; Ellen Carolina Putri Daeli; Noriwati Lase; Irene Zega; Putri Amirah Hafidz Harefa; Azeti Harefa; Maria Magdalena Bate’e (Al-Qalam Institute, 2025)
This research aims to explore the role of education in increasing the success of gold investment in central poin. Gold has historically been a reliable asset, particularly in developing countries like Indonesia, offering stability amidst economic volatility. However, despite its benefits, many local investors face challenges, such as fluctuating prices and the risk of fraud, which highlight the need for enhanced financial education. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather data from gold investors. The findings reveal that gold is considered a safe-haven investment amidst economic uncertainty, with educated investors more likely to view it as a means of portfolio diversification. Additionally, trust-building between local traders and investors is crucial for creating a stable investment environment. Furthermore, access to accurate and timely information significantly boosts investor confidence and decision-making. The study highlights the importance of investor education in mitigating risks and ensuring informed decision-making. Recommendations include increasing financial literacy programs and enhancing the accessibility of educational resources for local investors. This research contributes to the growing body of knowledge on gold investment and offers practical insights for both investors and local gold traders.